DEATH IN DYLAN THOMAS’S POEM “A REFUSAL TO MOURN THE DEATH, BY FIRE, OF A CHILD IN LONDON” AND ITS RELATION TO THE CHRISTIAN TRADITION - da Silva Cabral, Gladir (Publicatio UEPG: Ciências Sociais Aplicadas, 2009)
Dylan Thomas wrote several poems dealing with the problem of death. “A Refusal to Mourn the Death, by Fire, of a Child in London” is dedicated to a child, victim of bombardment in London during World War II. The objective of this article is to analyse Dylan Thomas’s attitude towards death according to this poem, and to compare it to the view of death according to the Christian tradition. In “A Refusal to Mourn the Death, by Fire, of a Child in London,” the persona laments the absurdity of a child’s death and, contradictorily, refuses to lament this death as if his lament were a profanation of its sacredness. Key words: war, death, grief, Christian tradition